Malawi’s challenging employment landscape: Any signs of structural transformation? Synopsis - Baulch, Bob; Benson, Todd; Erman, Alvina; Lifeyo, Yanjanani; Mkweta, Priscilla (International Food Policy Research Institute, 2019)
This policy note examines employment patterns for evidence of the extent to which a structural transformation is underway in Malawi. We explore whether Malawi’s labor force shifted out of the subsistence agriculture sector and into the industry and service sectors. To better understand the role of the large youth population in structural transformation, we assess the extent of youth employment in agriculture and in services, and the factors shaping their choices. We conclude with a discussion of how policy can support transformation and job creation for youth.